Biodiesel production from moringa oleifera seeds oil by using MgO as a catalyst - Aqwa, Nawi (2015)
Biodiesel is a RE (renewable energy) source derived alternative fuel for diesel engine application that is produced through the transesterification of vegetable oil, animal fats or waste vegetable oil with alcohol in the presence of catalyst. Moringa oleifera seeds can be used for biodiesel production by transesterification using magnesium oxide (MgO) as a solid base catalyst. Therefore, this study is conducted to investigate the possible production of biodiesel by using Moringa oleifera seeds oil through base catalyst method. A sample of 25 mL oil was poured into the 3-neck bottom flask. Carefully, the methanol was poured into the oil with ratios of 8:1, 10:1, and 12:1 methanol to oil for the transesterification process. The MgO was used with different concentration of, 0.5%, 0.7%, 1.0% w/w. As a result, the methyl ester (biodiesel) produced by using Moringa oleifera seeds oil exhibits a high yield by using 60-70°C reaction temperature, 1.5 hour reaction periods, and 200 rpm mixing rate. As the result, about 60% yield of biodiesel was produced using 0.5 wt% catalyst concentration and 12:1 methanol to oil ratio. In conclusion, biodiesel production by using Moringa oleifera seeds oil appear to be an acceptable alternative fuel as well as renewable source of energy for the future use.